Frequency of Low-level Mosaicism in X-Cromosome in Couples with Antecedent of Recurrent Miscarriages - Maribel Forero C.., Elkin Lucena Q. M.D., PhD., Clara Esteban Pérez BSc., MSc (Revista Ciencias de la Salud, 2006)
Recurrent miscarriage occurs in around 1 to 7percent of couples. The etiology involves genetic,immunologic, anatomic, hormonal, metabolic,thrombophilic and infectious factors. With theaim of establishing the frequency of low-level mosaicism in the X-chromosome, in a populationof couples with prior recurrent miscarriages, aprospective case-control cytogenetic study tookplace on 20 couples, at the biogenetic laboratoryin CECOLFES (Colombian Center of Fertility andSterility). Clinical pathologic evaluation, anatomic,hormonal, infectious, andrologic and geneticstudies were performed. As a conventionalmethod in cytogenetic techniques, banding GTGwas used for the study of structural and numericchromosomal abnormalities whereas the molecularmethod of Fluorescence In Situ Hybridization(FISH) was used to confirm the mosaicismin sexual chromosomes. According to paraclinicresults from the participating couples, diagnosisshowed immunologic (75%), anatomic (30%),hormonal (25%), male (25%), infectious (25%),genetic (15%) and idiophatic factors (10%).Results from the cytogenetic analysis, were 10%of low-level mosaicism in the X-chromosome intwo women whose final diagnosis includedgenetic and infectious factors for one and geneticand immunologic factors for the other. Only 10% of the total miscarriages from the couples wereevaluated. Conclusions include aspects such asmultifactorial evidence of pathogenesis in recurrentmiscarriage, the sub-diagnosis of geneticfactors and the need to focus future investigationson cytogenetic interpretation and the clinicalpathologicalassociation between low-level mosaicismin the X-cromosome and recurrentmiscarriage.